REVOLUSI INDUSTRI 4.0: DAMPAK TEKNOLOGI PADA DUNIA KERJA PADA SMK NEGERI 8 TANGERANG SELATAN - Achmad Fadhilah Shidiq; Ahmad Baihaqi; Alfi Ardiansyah; Ananda Zahratun Nisa; Chakra Yoga Pambayun; Atin Suprihatni; M. Saepul Azis; Muhammad Rifqi Saifulloh; Ramadhan Fardien Hasan; Rizal Muhamad Ikhwanudin Ady (Abdi Jurnal Publikasi, 2025)
The Industrial Revolution 4.0 brings significant changes to the world of work, especially for vocational high school students who need to adapt to the integration of digital technology. Through this seminar, students of SMKN 8 Tangerang Selatan were given an in-depth understanding of technologies such as AI and IoT as well as the skills needed to compete in the digital era. This community service activity included presentations, discussions, and interactive quizzes aimed at increasing students' awareness and readiness to face industry challenges. In conclusion, this seminar effectively equipped participants with relevant knowledge and skills to face the ever-changing world of work.